Active plasma renin concentration throughout healthy and complicated pregnancy: a systematic review and meta-analysis - Wisal El Fathi; Maaike van Ochten; Munieb Rehman; Sander M. J. van Kuijk; Joanna IntHout; Chahinda Ghossein-Doha; Sander de Haas; Marc E. A. Spaanderman; Joris van Drongelen (BMC, 2024)
Abstract Background Pregnancy is characterized by profound circulatory changes and compensatory adjustments in the renin-angiotensin-aldosterone system (RAAS). Differences in regulatory response may antedate or accompany vascular complicated pregnancy. We performed a systematic review and meta-analysis to delineate the trajectory of active plasma renin concentration (APRC) in healthy pregnancy and compare this to complicated pregnancy. Methods We performed a systematic review and meta-analysis on APRC during normotensive and hypertensive pregnancies, using PubMed (NCBI) and Embase (Ovid) databases. We included only studies reporting measurements during pregnancy together with a nonpregnant reference group measurement. Risk of bias was assessed with QUIPS. Ratio of the mean (ROM) and 95% confidence intervals (CI) of APRC values between pregnant and nonpregnant women were estimated for predefined intervals of gestational age using a random-effects model. Meta-regression was used to analyze APRC over time. Results In total, we included 18 studies. As compared to nonpregnant, APRC significantly increased as early as the first weeks of healthy pregnancy and stayed increased throughout the whole pregnancy (ROM 2.77; 95% CI 2.26-3.39). APRC in hypertensive complicated pregnancy was not significantly different from nonpregnancy (ROM 1.32; 95% CI 0.97-1.80). Conclusion Healthy pregnancy is accompanied by a profound rise in APRC in the first trimester that is maintained until term. In hypertensive complicated pregnancy, this increase in APRC is not observed.